Application of 'Scenario Strategic Planning' as development tool in community-based tourism - Chalermchai , Panyadee; Parnprae , Chaoprayoon (2013)
This research was a study on the Scenario Strategic Planning and its application for community-based tourism. The study aimed to apply the Scenario Strategic Planning to reinforce the strength of a community-based tourism management. This research was a combination of qualitative and quantitative methods which was conducted at the Ban Phamon Village, Chomthong district, Chiang mai province, and Ban Santichon Village, Pai district, Mae Hong Son province. Both of the villages used the Scenario Planning as instrument for the development of Community-based tourism. The villagers had helped each other to carry out, perceive, and use the plan together. Tourism industry is one of the very important industries in Thailand that continuously create jobs and revenues for people in the country. However, the changing of tourism industry is very dynamic and competitive with the float of globalization which impacts the local level tourism industry, especially, the non-prepared community which could not support these changes concerning political, economic, socio-cultural and technological thoughts. These effects cost community’s benefit to decrease and the lack of growing with negative impacts, also, the community may have loosened their local culture as well. The aforementioned problems, however, could be solved or prevented by applying planning techniques in which this research found that the Scenario Planning is one of the most practical techniques and instrument to be used in development planning such that it can decrease the negative impacts of the community and simultaneously assist the community to support tourism industry as well as to identify the problems and determine solutions for equitable distribution of profits. Results in both of the research sites proved that the application of the Scenario Planning for Community-based tourism could be very useful. Result of study further reveal that solutions seemed to be the unity and the readiness of the community to solve the problems via strengthening of the community through participatory activities as a development activity, where the application of Scenario Strategic Planning becomes very effective. In conclusion, this research article would bring the presentation of the Scenario Strategic Planning to strengthen the power of the community towards tourism management. In short, the community would manage to organize the natural and the cultural resources for the tourism industry.